Comment on: Role of 68-Ga-PSMA-PET/CT in pelvic radiotherapy field definitions for lymph node coverage in prostate cancer patients, by Onal C et al. (February 2021) - Goyal, Shikha; Madan, Renu
Highlights: Nodal radiotherapy in prostate cancer is a topic of debate. Patterns of relapse indicate that the current target delineation recommendations underestimate and under-cover the nodal involvement. PSMA PET-CT may help map the nodal involvement patterns with good sensitivity and specificity even outside the conventional recommended volumes and may serve as guides to surgical dissection as well as radiation therapy.